Pendampingan Artikel Ilmiah: Tips Dan Trik Tembus Jurnal Sinta - Sabariah, Sabariah; Yanto, Yanto; Baidowi, Ach.; Uzliva, Citra Aulia; Hotimah, Nur (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2024)
The aim of mentoring scientific articles is to improve the structure and content of articles owned by lecturers or students. The implementation method is face to face for 5 hours using laptop equipment, LCD projector, sound system, materials. Implementation results: the first material regarding the title is written in a maximum of 15 words, the abstract is written briefly and the keywords are written in a maximum of 5 words or phrases. The second material regarding the introduction must explain the specific research objectives and research methods that meet a minimum of 4 qualitative elements and 6 quantitative elements. The third material concerns the results and discussion which must be prepared based on the subject matter and conclusions which must be prepared without repeating the research results. The fourth material is about citations and bibliography which must be prepared by memorizing a form of citation. The overall conclusion was that the implementation of the service was successful and had a positive impact, namely that participants better understood how to write good articles according to national accreditation journal standards.